Using commercially available off-the-shelf software and hardware to develop an intranet-based hypertext markup language teaching file...Proceedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: performance improvement in radiology.' Houston TX, May 6-9, 1999 - Wendt GJ (Journal of Digital Imaging)
This presentation describes the technical details of implementing a process to create digital teaching files stressing the use of commercial off-the-shelf (COTS) software and hardware and standard hypertext markup language (HTML) to keep development costs to a minimum. Copyright (c) 1999 by W.B. Saunders Company